-6целыых2/3-8.75-2целых5/12

-6целыых2/3-8.75-2целых5/12
Гость
Ответ(ы) на вопрос:
Гость
−6целых 2/3 −2целых5/12 =−6 · 3 + 2/3    −2 · 12 + 5/12 =−20/3 −29/12 =−4 · 20/4 · 3     −1 · 29/1 · 12 =−80/12 −29/12 =-80 − 29/12 =−109/12 =−91/12 −91/12   ≈ −9,083 −9,083-8.75= -17.833 -8.75= -8целых3/4 -91/12-(-8целых3/4)= −91/12 −(−8целых3/4) =−91/12 +8целых3/4 =−91/12 +8 · 4 + 3/4 =−91/12 +35/4 =−1 · 91/1 · 12 +3 · 35/3 · 4 =−91/12 +105/12 =-91 + 105/12 =14/12 =7/6 =1целая1/6 1целая1/6  ≈ 1,167 Хочешь дробью, хочешь десятичным числом запиши ответ.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы